Quo vadis global forest governance? A transdisciplinary delphi study. Issue 123 (September 2021) - Begemann, A.; Giessen, L.; Roitsch, D.; Roux, J.-L.; Lovrić, M.; Azevedo-Ramos, C.; Boerner, J.; Beeko, C.; Cashore, B.; Cerutti, P.O.; de Jong, W.; Fosse, L.J.; et al.
Highlights: Deforestation and forest degradation remain the most prominent challenges in global forest governance. In a multipolar world, issue specific coalitions across world regions are critical for global forest governance. Governance initiatives connecting to "high politics" such as trade are promising for global forest governance. Both investment and informal markets are not sufficiently accounted for in global forest governance. New information technologies can increase transparency in global forest governance. Abstract: Deforestation and forest degradation remain huge global environmental challenges. Over the last decades, various forest governance initiatives and institutions have evolved in global response to interlinked topics such as climate change mitigation, biodiversity conservation, indigenous rights, and trade impacts – accompanied by various levels of academic attention. Using a Delphi methodology that draws on both policy and academic insights, we assess the currently perceived state of play in global forest governance and identify possible future directions. Results indicate that state actors are seen to be key in providing supportive regulatory frameworks, yet interviewees do not believe these will be established at the global scale. Rather, respondents point to issue-specific, regional and inter-regional coalitions of the willing, involving the private sector, to innovate global forest governance. Linking forest issues with high politics may hold promise, as demonstrated by initiatives regarding illegal logging and timber trade. Confident rule-setting in support of the public good as well as responsible investments are seen as further avenues. New forest governance "hypes", if used strategically, can provide leverage points and resources to ensure sustainability effects on the ground. At the same time, informal markets are often crucial for governance outcomes and need consideration. As such, clarifying tenure in sovereignty-sensitive ways is important, as are innovative ways for inclusive "glocal" decision-making. Lastly, new technologies, big data and citizens' capacities are identified as potent innovation opportunities, for making global dependencies between consumption, production and deforestation visible and holding players accountable across the value chains.